Parental Perspectives on Children's Second Language Learning: Insights, Challenges, and Expectations - Setiawan, Anjar; Rusiana, Rusiana; Jingwangsa, Piyada (Educalingua Journal, 2025)
This study investigates how parents support their children's second language (L2) learning in Indonesian bilingual and English-enriched primary schools, using Vygotsky’s Sociocultural Theory and the concept of parental involvement. Involving 27 parents, the research used interviews and observations to explore how their motivations, attitudes, and practices influence children’s L2 development. The findings highlight three key parental roles: motivator, learning facilitator, and resource provider. Most parents showed positive attitudes toward bilingualism and were eager to help their children learn English. However, differences in socioeconomic status, education, and language skills influenced how actively and effectively they could be involved. The study emphasizes the importance of strengthening home-school collaboration and suggests inclusive strategies to help all parents—regardless of background—support their children’s language learning in multilingual contexts.